Comparative Pharmacokinetic Studies of Fast Dissolving Film and Oral Solution of Ondansetron in Rats - R. Choudhary, Dhagla; A. Patel, Vishnu; K. Chhalotiya, Usmangani; V. Patel, Harsha; J. Kundawala, Aliasgar (Current Drug Delivery, 2013)
Ondansetron, selective serotonin (5-HT3) receptor blocker, is used in treating chemotherapy induced nausea and vomiting in cancer patients. Mouth dissolving films containing ondansetron were developed to have better onset and patient compliances. The drug content of prepared films was within 85%-115%. The films were found to be stable for 4 months when stored at 40 °C and 75% RH. In-vitro dissolution studies suggested a rapid disintegration, in which most of ondansetron was released (91.5±3.4%) within 90 sec. Subsequently, Sprague–Dawley rats were used to compare pharmacokinetic parameters of the formulated films with oral administration of pure drug solution. Pharmacokinetic parameters were similar between the two groups in which AUC0-t (ng h/ml), AUC0-∞ (ng h/ml), Cmax (ng/ml), Tmax (min), Kel (h-1) and t1/2 (h) of reference was 109.091±15.73, 130.32±18.56, 28.5±4.053, 60, 0.1860±0.0226, and 3.771±0.498 respectively; and for formulated film 113.663±16.64, 151.79±16.54, 30±3.51, 60, 0.1521±0.0310 and 4.755±0.653 respectively. These results suggest that the fast dissolving film containing ondansetron is likely to become one of the choices to treat chemotherapy induced nausea and vomiting.
Keywords: Drug content